The Relationship between Elderly Characteristics and the Incidence of Cough in Elderly Residents at Social Institution X in Jakarta: A Cross-Sectional Analysis - Rayhana Rayhana; Resy Dwi Aprilianti; Adinta Anandani; Dayu Swasti Kharisma; Jihan Samira (Research of Service Administration Health and Sains Healthys, 2026)
Cough is one of the respiratory complaints that often occurs in the elderly and can reduce the quality of life if it occurs chronically. This study aims to analyze the relationship between elderly characteristics and the incidence of cough in Social Institution X. The study used an observational analytical design with a cross-sectional approach. The study sample consisted of 110 respondents selected using a purposive sampling technique. Data analysis was performed using IBM SPSS Statistics version 26 through univariate and bivariate analysis with the chi-square test at a significance level of p<0.05. The results showed that most respondents were in the 60–74 years age group (70.9%), female (66.4%), had normal nutritional status (51.8%), and did not have a smoking habit (53.9%). Most respondents did not experience cough (50%). Bivariate analysis showed that nutritional status and smoking habits were significantly associated with the incidence of cough in the elderly (p<0.05), while age and gender did not show a significant relationship (p>0.05). This study emphasizes the importance of controlling risk factors and implementing a healthy lifestyle in efforts to prevent respiratory disorders in the elderly.